Mega Korupsi Tata Niaga Timah Rp 300 Triliun: Analisis Pelanggaran Prinsip Pancasila dan Etika Tata Kelola Dalam Pengelolaan Sumber Daya Alam - Ricky Fairuz Julio; Sri Isnani Setyaningsih (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
The Rp 300 trillion tin trade mega-corruption case is one of the largest corruption scandals in the history of Indonesian natural resource management. This study aims to analyze violations of Pancasila principles and ethical governance in the tin trade mega-corruption case, and to identify threats to Indonesian natural resource management. The study uses a qualitative approach with descriptive methods. Data were collected through documentary studies of law enforcement reports, government documents, media reports, and related literature. Data analysis was conducted thematically within the theoretical framework of Pancasila, good governance, and public ethics. The findings indicate that this case violates all of Pancasila's tenets, particularly the second (Just and Civilized Humanity) and fifth (Social Justice for All Indonesian People). There were violations of governance principles including transparency, accountability, participation, the rule of law, and effectiveness. The modus operandi involved collusion between business actors, state officials, and law enforcement officers. The mega-allegations reflect a systemic failure in natural resource management that contradicts the constitutional mandate and Pancasila values. Structural reforms are needed in mining governance, enforcement of the integrity of the apparatus, and public participation in supervision.